Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines the competitiveness of the Irish manufacturing sector. The paper highlights that in 2001, production cuts and accelerating wage growth arrested the trend improvement in external competitiveness, but the level remains high. The paper presents some medium-term fiscal scenarios. It discusses indicators of financial system soundness based on official data and publications, as well as discussions with the authorities. The paper also examines indicators on the vulnerability and solvency of the financial system and presents a brief description of supervision arrangements.